Left Ventricular Diastolic Dysfunction Is Not Associated With Pulmonary Edema in Septic Patients. A Prospective Observational Cohort Study - Kahl, Ursula; Schirren, Leah; Yu, Yuanyuan; Lezius, Susanne; Fischer, Marlene; Menke, Maja; Sinning, Christoph; Nierhaus, Axel; Vens, Maren; Zöllner, Christian; Kluge, Stefan; Goepfert, Matthias S.; et al. (Frontiers in Cardiovascular Medicine, 2022)
Purpose: We aimed to investigate whether left ventricular diastolic dysfunction (LVDD) is associated with pulmonary edema in septic patients. Methods: We conducted a prospective cohort study in adult septic patients between October 2018 and May 2019. We performed repeated echocardiography and lung ultrasound examinations within the first seven days after diagnosis of sepsis. We defined LVDD according to the 2016 recommendations of the American Society of Echocardiography and – for sensitivity analysis –according to an algorithm which has been validated in septic patients. We quantified pulmonary edema using the lung ultrasound score (LUSS), counting B-lines in four intercostal spaces. Results: We included 54 patients. LVDD was present in 51 (42%) of 122 echocardiography examinations. The mean (±SD) LUSS was 11 ± 6. There was no clinically meaningful association of LVDD with LUSS (B = 0.55 [95%CI: -1.38; 2.47]; p = 0.571). Pneumonia was significantly associated with higher LUSS (B = 4.42 [95%CI: 0.38; 8.5]; p = 0.033). Conclusion: The lack of a clinically meaningful association of LVDD with LUSS suggests that LVDD is not a major contributor to pulmonary edema in septic patients.